Rachael & Vilray [compact disc] - Price, Rachael, 1985-; Vilray, (Musician); Batiste, Jon, 1986- (Nonesuch Records, 2019)
The debut album by Lake Street Dive singer-songwriter Rachael Price and composer, singer, and guitarist Vilray features ten originals by Vilray, along with two covers from the era that inspired him: Cuban composer Pedro Junco Jr.'s 1943 Nosotros and Milton Drake/Louis Atler's I Love the Way You're Breaking My Heart, first popularized by Peggy Lee.